A new pyrimidine alkaloid from the roots of Tadehagi triquetrum (L.) H.Ohashi. Issue 3 (1st February 2021) - , Vedpal; Jupudi, Srikanth; Jubie, S.; Deepika, N. P.; Dhanabal, S. P.
Abstract: Tadehagi triquetrum (L.) H.Ohashi, also known as Desmodium triquetrum (Fabaceae) is the most important plant in the herbal remedies. The present study focus on the isolation, in-silico and in-vitro studies of the two alkaloids C1 (5-(4-[(methylcarbamoyl) amino]-2-oxopyrimidin-1(2 H )-yl) tetrahydrofuran-2-yl) methyl methyl carbamate is novel alkaloid and C2 13-Docosenamide is a known alkaloid. The chemical structures of compounds have been elucidated based on comprehensive techniques like GCMS, IR and NMR. In order to know the molecular mechanisms for the two compounds, in silico molecular docking study has been performed. Both compounds have shown perfect binding affinity to the enzymes TNF α, IL-4, IL-13 and 5 LOX Enzyme. The compounds also exhibited comparable G-scores and Glide energy values in comparison with the standard dexamethasone. In addition both the compounds have been tested for in vitro antioxidant assay by using ABTS and DPPH method and the results were compared with standard ascorbic acid. Graphical Abstract: